Insights into membrane distillation application for textile wastewater treatment – A review - Muhamad, N. A. S.; Hanoin, M. A. H. M.; Nadzirah, Mohd Mokhtar; Rosmawati, Naim (Universiti Teknologi Malaysia, 2021)
Textile wastewater must be effectively treated with the best available technology prior to release to receiving water bodies to prevent its impact on the environment. Apparently, membrane distillation shows great potential in treating textile wastewater a part of the complexity of the textile wastewater composition. This membrane process enables the water vapour to pass through its porous hydrophobic membrane and retains the concentrated pollutants to be transported. This paper provides data and information from previous studies using membrane distillation to treat textile wastewater. An overview of the development of membrane distillation as well as the fundamental theory is presented. Recent progress in the application of membrane distillation in textile wastewater is then discussed. The final part of the paper looked at the future orientation of this technology to be acceptable in the industrial sector, especially for the textile industry.